The competitiveness of nations: a different countries has different growth / Nickhlos Jalang - Jalang, Nickhlos (2016)
As we know, there is different type of country. However, why do some countries have better performance and grow so faster than the other. As we know, Malaysia is one of the developing countries which are also including China and Republic Korea has under the same categories. However, the developing country had a long journey to become a developed country. This is because of developing country growth had a huge different compare to developed country. This paper will estimate what the factor that could be and also what the government can do about it to increase their performance and through five different aspect of competitiveness which is Export of the Country (EXP), Global Manufacturing Competitiveness (GMC), Global Tax and Doing Business Index (GTDBI), Global Risk Monitor Index (GRMI), and Better Life Index (BLI). The framework is applied to a sample of nine countries which have been categories as three groups between 2010 and 2015 which is United State, Germany, Australia, China, Republic Korea, Malaysia, Nepal, Bangladesh, and Afghanistan. This study also will be conducted due to the theory of the growth and previous study that have a significant with this study. Then, the dataset will be tested by using Panel data tool and will be translated in the table to know the factor that could affect the growth which is by using the Gross Domestic Product (GDP).